ftz-f1 and Hr39 opposing roles on EcR expression during Drosophila mushroom body neuron remodeling. - Boulanger, A.; Clouet-Redt, C.; Farge, M.; Flandre, A.; Guignard, T.; Fernando, C.; Juge, F.; Dura, J.M. (Nature Neuroscience, 2011)
Developmental axon pruning is a general mechanism that is required for maturation of neural circuits. During Drosophila metamorphosis, the larval-specific dendrites and axons of early ? neurons of the mushroom bodies are pruned and replaced by adult-specific processes. We found that the nuclear receptor ftz-f1 is required for this pruning, activates expression of the steroid hormone receptor EcR-B1, whose activity is essential for ? remodeling, and represses expression of Hr39, an ftz-f1 homologous gene. If inappropriately expressed in the ? neurons, HR39 inhibits normal pruning, probably by competing with endogenous FTZ-F1, which results in decreased EcR-B1 expression. EcR-B1 was previously identified as a target of the TGF? signaling pathway. We found that the ftz-f1 and Hr39 pathway apparently acts independently of TGF? signaling, suggesting that EcR-B1 is the target of two parallel molecular pathways that act during ? neuron remodeling.